Endothelial Ribonuclease 1 in Cardiovascular and Systemic Inflammation - Bedenbender, Katrin; Schmeck, Bernd T. (Frontiers in Cell and Developmental Biology, 2020)
The vascular endothelial cell layer forms the inner lining of all blood vessels to maintain proper functioning of the vascular system. However, dysfunction of the endothelium depicts a major issue in context of vascular pathologies, such as atherosclerosis or thrombosis that cause several million deaths per year worldwide. In recent years, the endothelial extracellular endonuclease Ribonuclease 1 (RNase1) was described as a key player in regulation of vascular homeostasis by protecting endothelial cells from detrimental effects of the damage associated molecular pattern extracellular RNA upon acute inflammation. Despite this protective function, massive dysregulation of RNase1 was observed during prolonged endothelial cell inflammation resulting in progression of several vascular diseases. For the first time, this review article outlines the current knowledge on endothelial RNase1 and its role in function and dysfunction of the endothelium, thereby focusing on the intensive research from recent years: Uncovering the underlying mechanisms of RNase1 function and regulation in response to acute as well as long-term inflammation, the role of RNase1 in context of vascular, inflammatory and infectious diseases and the potential to develop novel therapeutic options to treat these pathologies against the background of RNase1 function in endothelial cells.